![y''-y'-2y=-e^t](https://img.qammunity.org/2020/formulas/mathematics/college/2phfm71wfki0uwkblk91sq4skfbnjft6aa.png)
The corresponding homogeneous ODE is
![y''-y'-2y=0](https://img.qammunity.org/2020/formulas/mathematics/college/bi7h39q1gqjdkpkjs09bocdo2rhzmld7vb.png)
with characteristic equation
![r^2-r-2=(r-2)(r+1)=0](https://img.qammunity.org/2020/formulas/mathematics/college/cwyhp5v3nszogjwaan74zj0ueoumyi8vo1.png)
with roots at
and
, so the characteristic solution is
![y_c=C_1e^(2t)+C_2e^(-t)](https://img.qammunity.org/2020/formulas/mathematics/college/gfy4klzlmq551xl87hv208dzw379bnhsex.png)
For the non-homogeneous ODE, assume a particular solution of the form
![y_p=ae^t](https://img.qammunity.org/2020/formulas/mathematics/college/3gcgn4kfys0gnzpbhk8pafyj886u13o4sn.png)
![\implies{y_p}'=ae^t](https://img.qammunity.org/2020/formulas/mathematics/college/qbztxjgot0vmwgd9fh4joke9lrkyrxfg0q.png)
![\implies{y_p}''=ae^t](https://img.qammunity.org/2020/formulas/mathematics/college/5jtib2bmn1h6g2mr0n7olj63lq3hro92hp.png)
Substituting
and its derivatives into the ODE gives
![ae^t-ae^t-2ae^t=-e^t](https://img.qammunity.org/2020/formulas/mathematics/college/9h4aoemta6budqo1267u0p8lnaj7nln26d.png)
![-2ae^t=-e^t](https://img.qammunity.org/2020/formulas/mathematics/college/3ox7mrqb1a1xg6g8391d1op1bwss7qzabo.png)
![\implies-2a=-1\implies a=\frac12](https://img.qammunity.org/2020/formulas/mathematics/college/p6v9jfzdekp5a1xqjsymiuedr9l0xrt6o8.png)
Then the ODE has the general solution
![\boxed{y(t)=C_1e^(2t)++C_2e^(-t)+\frac12e^t}](https://img.qammunity.org/2020/formulas/mathematics/college/6xk0rjqh4cv3nli7lwsby6kx3lzst91fak.png)